2022
DOI: 10.1038/s41598-022-18971-6
|View full text |Cite
|
Sign up to set email alerts
|

The healthy equine uterus harbors a distinct core microbiome plus a rich and diverse microbiome that varies with geographical location

Abstract: The goal of this study was to understand the composition and existence of the resident uterine microbiome in healthy mares and to establish the presence of a core microbiome for the healthy equine uterus. We analyzed the microbiomes of 35 healthy mares that are long-time residents of three farms in Oklahoma, Louisiana, and Australia as well as that of 19 mares purchased from scattered owners in the Southern Mid-Western states of the United States. Over 6 million paired-end reads of the V4 region of the 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 62 publications
10
14
0
Order By: Relevance
“…The detection of a diverse uterine microbiome in healthy mares in the present study, together with the findings of previous studies (Heil et al, 2018; Holyoak et al, 2022), strongly refutes the dogma of a sterile uterus in healthy mares. The composition of the uterine microbiome in the healthy mares in this study was mostly similar to that reported in a previous study in horses (Holyoak et al, 2022) and studies in other domestic animal species such as cows (Clemmons et al, 2017; Moore et al, 2017) and dogs (Lyman et al, 2019). Similar to the findings of Holyoak et al (2022), proteobacteria and firmicutes constituted a vast majority of the uterine microbiome.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The detection of a diverse uterine microbiome in healthy mares in the present study, together with the findings of previous studies (Heil et al, 2018; Holyoak et al, 2022), strongly refutes the dogma of a sterile uterus in healthy mares. The composition of the uterine microbiome in the healthy mares in this study was mostly similar to that reported in a previous study in horses (Holyoak et al, 2022) and studies in other domestic animal species such as cows (Clemmons et al, 2017; Moore et al, 2017) and dogs (Lyman et al, 2019). Similar to the findings of Holyoak et al (2022), proteobacteria and firmicutes constituted a vast majority of the uterine microbiome.…”
Section: Discussionsupporting
confidence: 89%
“…The composition of the uterine microbiome in the healthy mares in this study was mostly similar to that reported in a previous study in horses (Holyoak et al, 2022) and studies in other domestic animal species such as cows (Clemmons et al, 2017; Moore et al, 2017) and dogs (Lyman et al, 2019). Similar to the findings of Holyoak et al (2022), proteobacteria and firmicutes constituted a vast majority of the uterine microbiome. However, there were some differences at the genus and species levels, which could be attributed to different geographical locations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Different parts of the reproductive tract in mammals have been shown to harbor their own distinct microbiota and a wide variety of opportunistic and pathogenic bacteria [ 1 ]. In large animals, uteri can potentially be contaminated with considerable loads of microorganisms during late gestation and throughout the postpartum period, and the respective phyla can fluctuate during the following periods and at different times of the estrous cycle [ 2 , 3 ]. The contaminating bacteria may or may not underpin uterine infections depending mainly on the type and number of the bacteria, presence of virulence factors and the host response to contamination [ 4 , 5 , 6 ] and should infection develop, they could eventually lead to significant reproductive losses by adversely affecting the follicular growth [ 7 , 8 ], conception rate and embryo survival [ 9 , 10 ] and disturbing normal hormonal profile of the affected animals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%